2011
DOI: 10.1002/jrs.2852
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic study of various types of tourmalines

Abstract: Both polarized and unpolarized Raman scattering studies of seven tourmalines from the Lucyen mines in Vietnam are presented. These tourmalines, according to their chemical compositions, can be classified into four groups: G1, liddicoatite; G2, elbaite; G3, uvite; and G4, feruvite. The Raman spectra were recorded in two spectral ranges, i.e. 150-1600 cm −1 and 3000-4000 cm −1 . In the lower spectral range, which covers the metal ion-oxygen bond vibrations, all the observed A 1 and E modes are identified. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 13 publications
3
18
0
Order By: Relevance
“…9,13 Its magnetic phases are characterized by various antiferromagnetic states such that the first antiferromagnetic phase appears below T N3 ≈ 13.5 K. Successive magnetic phase transitions occur at T N2 ≈ 12.5 K and T N1 ≈ 6.5-8 K, forming three different antiferromagnetically ordered phases: AF1 (T ≤ T N1 ), AF2 (T N1 ≤ T ≤ T N2 ), and AF3 (T N2 ≤ T ≤ T N3 ). 14,15 These magnetic phases have been characterized by neutron scattering experiments, which have shown that AF1 has a collinear up-up-down-down spin structure, AF2 has a non-collinear spiral spin structure, and AF3 has a sinusoidal collinear spin structure.…”
Section: 10mentioning
confidence: 99%
See 1 more Smart Citation
“…9,13 Its magnetic phases are characterized by various antiferromagnetic states such that the first antiferromagnetic phase appears below T N3 ≈ 13.5 K. Successive magnetic phase transitions occur at T N2 ≈ 12.5 K and T N1 ≈ 6.5-8 K, forming three different antiferromagnetically ordered phases: AF1 (T ≤ T N1 ), AF2 (T N1 ≤ T ≤ T N2 ), and AF3 (T N2 ≤ T ≤ T N3 ). 14,15 These magnetic phases have been characterized by neutron scattering experiments, which have shown that AF1 has a collinear up-up-down-down spin structure, AF2 has a non-collinear spiral spin structure, and AF3 has a sinusoidal collinear spin structure.…”
Section: 10mentioning
confidence: 99%
“…Moreover, our observation is consistent with the recent Raman studies, where Raman active phonons likewise do not show an anomaly across the magnetic and ferroelectric transition temperatures. 13,31 Therefore, a direct relation between the phonon spectral features and the magnetoelectric coupling properties in MnWO 4 could not be identified.…”
Section: B Optical Phonon Structure Of Mnwomentioning
confidence: 99%
“…Besides garnets as simulant of rubies, among the studied gems, a tourmaline was also identified [sample R14, Fig. (b)] by its Raman spectrum,exhibiting the main peaks at about 377, 730 and 1070 cm −1 …”
Section: Resultsmentioning
confidence: 99%
“…Besides garnets as simulant of rubies, among the studied gems, a tourmaline was also identified [sample R14, Fig. 3(b)] by its Raman spectrum, [17] exhibiting the main peaks at about 377, 730 and 1070 cm À1 . [18] In the case of sample R11, several strong photoluminescence bands as well as the absence of well-structured peaks were detected, suggesting that the gem was a glass imitation [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectroscopy is a widely applied method for the identification of minerals as well as recognition of their compositional relationships; it is also used frequently in studies of tourmalines [36][37][38][39][40][41][42][43][44]. Because of the particular location of OH groups, which are bound to the octahedral Y and Z cations in the tourmaline structure, the OH vibration bands code crystallochemical information on occupation of both octahedral sites.…”
Section: Raman Spectroscopymentioning
confidence: 99%